PUASA SEBAGAI KOMUNIKASI SPIRITUAL DAN SOSIAL: MEMBANGUN HUBUNGAN DENGAN ALLAH DAN SESAMA (PERSPEKTIF AL-QURAN SURAH AL-BAQARAH AYAT 183) - Syarifudin (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
Fasting in Islam is not merely a physical ritual but also a form of spiritual communication with Allah and a tool to strengthen social relationships among people. This research aims to examine how fasting serves as a medium for vertical communication (hablum minallah) and horizontal communication (hablum minannas). The research method used is a qualitative approach based on a literature review, analyzing classical and contemporary sources such as the interpretations of Ibn Kathir, Qurtubi, Tabari, Sayyid Qutb, Quraisy Shihab, and Nawawi Al-Bantani. The study's findings indicate that fasting creates a unique dimension of communication in Islam. Spiritually, fasting teaches obedience, sincerity, and closeness to Allah. Ibn Kathir highlights that fasting is a direct form of worship evaluated by Allah alone. Socially, fasting instills empathy, togetherness, and solidarity within the community. Quraisy Shihab explains that fasting encourages individuals to understand the suffering of the less fortunate, fostering social awareness. By understanding fasting as a means of spiritual and social communication, Muslims can deepen their appreciation of this worship in daily life. Keywords: Fasting; Spiritual Communication; Social Communication; Empathy; Solidarity.